Ok or Not Ok: Mental Health Conditions of the Students amidst COVID-19 - Arbiol, Jennifer M.; Cabajes, Angelie V.; Pusta, Rey Jan S. (Technium Social Sciences Journal, 2021)
The study aims to determine the mental health conditions experienced by the participants during the pandemic and identify the number of severe cases for appropriate intervention. It hypothesizes that the mental conditions of the participants vary when compared to gender. A total of 1,113 students participated in the study. A checklist was developed based on the DSM-V symptoms for major depressive disorder and generalized anxiety disorder. Data were gathered using online platform, wherein purposive sampling was utilized as only those with internet access can answer the survey. Data were analyze using mean and frequency distribution, and Mann-Whitney Test. Results of the study revealed that participants experienced difficulty in concentrating and sleeping. A total number of 167 participants experienced severe symptoms of anxiety and depression. Mental health conditions of the participants were found to vary when compared to gender.